Decoupling the roles of constituent phases in the strengthening of hydrogenated nanocrystalline dual-phase high-entropy alloys. (15th March 2022) - Gao, Zhe; Zhao, Yakai; Park, Jeong-Min; Jeon, A-Hyun; Murakami, Kotaro; Komazaki, Shin-ichi; Tsuchiya, Koichi; Ramamurty, Upadrasta; Jang, Jae-il
Abstract: Nanocrystalline (NC) dual-phase Al0.7 CoCrFeNi HEAs containing face-centered cubic (FCC) and body-centered cubic (BCC) microstructural phases were fabricated by high-pressure torsion (HPT). The influences of hydrogen on the thermal desorption and nanoindentation responses of NC HEA were compared with the coarse-grained alloy. The plastic zone size and indentation size effects were carefully considered to identify the distinct contributions of the constituent phases to the hardness and its variation with hydrogen charging. Results show that the FCC phase is susceptible to a larger degree of hydrogen-induced hardening than the BCC phase. Such difference is negated in the NC samples. These results are discussed in terms of the distinct responses of FCC and BCC HEA phases to hydrogen and the governing deformation mechanisms in coarse grained and NC samples. Graphical abstract: Image, graphical abstract